2002
DOI: 10.2355/isijinternational.42.1571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure on the Yield Ratio and Low Temperature Toughness of Linepipe Steels.

Abstract: Linepipe steels, which transport oil and gas, should have high strength, high toughness, excellent corrosion resistance and superior weldability. [1][2][3] The current demand is towards the larger-diameter and higher-pressure linepipes to improve the efficiency of transmission, resulting in more stringent specifications for the linepipe steels. In addition to the above mentioned properties, the steels should have low yield ratio (yield strength/tensile strength) for the safety concern. The lower yield ratio me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(108 citation statements)
references
References 6 publications
1
89
0
Order By: Relevance
“…With the further application of pipeline steels in long-distance transportation and harsh environment, excellent toughness, weldability and deformability become more and more important, in addition to the high strength, to guarantee the safety [2][3][4]. Appropriate design of the microstructure is essential to achieve these targeted mechanical properties, which can be obtained by optimizing the chemical composition and the Thermo-Mechanical Control Processing (TMCP) schedule.…”
Section: Introductionmentioning
confidence: 99%
“…With the further application of pipeline steels in long-distance transportation and harsh environment, excellent toughness, weldability and deformability become more and more important, in addition to the high strength, to guarantee the safety [2][3][4]. Appropriate design of the microstructure is essential to achieve these targeted mechanical properties, which can be obtained by optimizing the chemical composition and the Thermo-Mechanical Control Processing (TMCP) schedule.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is a tendency at 500°C to have a higher fraction of secondary phases (martensite, austenite, degenerated pearlite (i.e. pearlite with an imperfect lamellar structure)), which will lead to a more continuous yielding behavior and a higher strain hardening, 18,19) which is also apparent in the lower yield ratio R p0.2 /R m . The austenite observed in most of the materials could in principle contribute to the strain hardening as well through Transformation Induced Plasticity (TRIP), but the volume fractions are quite low.…”
Section: Correlation Between Microstructure and Mechanical Propertiesmentioning
confidence: 99%
“…For lath bainite or martensite, the austenite grain is divided into packets (bundled by group of blocks with the same habit plane), and each packet is further subdivided into blocks (bundled by laths with the same orientation) [12][13][14]. Early works by Lee et al [15] and Kim et al [16] indicated that prior austenite is the effective microstructure unit in control of the toughness of bainite steels, and crack can propagate across the packet boundaries without changing the direction. On the contrary, studies by Wang et al [14] and Rancel et al [17] showed that packet boundaries can strongly hinder fracture propagation and can act as an effective microstructure unit in control of the toughness for cleavage fracture.…”
Section: Methodsmentioning
confidence: 99%
“…The studies by Wang et al [14] and Rancel et al [16] indicated that the packet boundaries can strongly hinder fracture propagation and can act as an effective microstructure unit for cleavage fracture. Moreover, in recent work by Yang et al [18,34], they revealed that high angle boundary (including packet boundary) remarkably contributes to a good toughness of the CGHAZ in high-grade pipeline steel.…”
Section: Effect Of Grain Boundary On Impact Toughness In the Simulatementioning
confidence: 99%